(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2024)
This paper proposes the design of Automatic vending machine. The main objective of our project is to launch new technology application in society. This is Arduino based vending machine that sales different type of chocolates from machine. This paper attempt to provide solution in coin based vending machine which is not returned the amount of money that is no any change from machine. The plan is to use Radio frequency Identification along with Arduino. Once RFID is to be read then User can select the product after card is scanned and collects the product at output unit. There are three parts; First part is scanning of RFID card which provides cashless payment. The second is programming unit which is implemented using arduino. The third part is display information and deliver product at output. This paper attempt to provide solution on coin based vending machine which is not returning the money.